Loving intensities: constant love and fleeting love. Or love-forever in both cases? - Martín Zorraquino, María Antonia (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This article analyzes a set of texts that show two manifestations of the love experience: utopian love, fleeting, ephemeral, in a fragment of the novel Gaudeamus (1986) ―a lyrical evocation― by José María Conget, and familiar love, experienced and lived, beautifully nuanced, in four poems by Ildefonso-Manuel Gil. It is concluded that, despite the apparent opposition between the two forms of love, the two reflect love forever, due to how strongly their experience is.